Impacts of land exclusion on women's socio-economic wellbeing in post-war Sri Lanka - Suheera, Mohamed Yaseen Minnathul; Wazeema, Thaseem Mohamed Fathima (Center for Sociological Studies and Community Developmen, 2025)
Land is widely considered a fundamental asset and provides economic and social security to women. Land-based access is complicatedly linked to various dimensions of women's well-being. The exclusion of women from land ownership or use of land creates limits to their ability in economic activities, and decision-making processes, leading to socio-economic inequalities. Before the war, women in Sri Lanka's Eastern Province owned land-based assets, ensuring economic welfare and social status. Post-war, their loss of land raises concerns about their economic strength. Therefore, this study aims to examine the impact of land exclusion on women's welfare in Batticaloa district, Sri Lanka, by using qualitative research methods. A purposive sampling was used, and the sample size was 25. In-depth interviews and focus group discussions were carried out to collect primary data and a thematic analysis was used for data analysis. The study found that most women were excluded from their land in the post-war context, leading to significant economic hardship, loss of rights, and social exclusion. Therefore, this study recommends a multidimensional approach to addressing the socio-economic impacts of land exclusion on women, including legal reforms, targeted support programs, and community-based initiatives.